DEVELOPMENT OF FUTURE TEACHERS’ SUBJECTIVITY IN THE CONTEXT OF PREPARATION FOR WORKING WITH GIFTED CHILDREN - Demchenko Оlena; Kit, Galina; Holiuk, Oksana; Rodiuk, Nataliia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The authors emphasize the importance of special training of future specialists in the psychological and pedagogical profile to the development of children's giftedness. Attention is focused on the importance of the formation of subjectivity as an integrative characteristic of the student. It is proved that in order to increase the activity of future teachers of gifted children during their preparation, it is necessary to make corrections in the methodology of organizing the educational process of the university. The experience of using modern technologies and techniques (business pedagogical games, case studies, “inverted training”, a portfolio of creative teacher, creative projects, individual research tasks of exploratory nature), attracting students to participation in scientific clubs and problem groups and to perform creative scientific works is theoretically grounded and shown in the process of forming them as the subjects of professional growth.